Behavioural economics and finance - Baddeley, Michelle, 1965- (New York : Routledge, 2019)
Behavioural economics and behavioural finance are rapidly expanding fields that are continually growing in prominence. While orthodox economic models are built upon restrictive and simplifying assumptions about rational choice and efficient markets, behavioural economics offers a robust alternative using insights and evidence that rest more easily with our understanding of how real people think, choose and decide. This insightful textbook introduces the key concepts from this rich, interdisciplinary approach to real-world decision-making. This new edition of Behavioural Economics and Finance is a thorough extension of the first edition, including updates to the key chapters on prospect theory; heuristics and bias; time and planning; sociality and identity; bad habits; personality, moods and emotions; behavioural macroeconomics; and well-being and happiness. It also includes a number of new chapters dedicated to the themes of incentives and motivations, behavioural public policy and emotional trading. Using pedagogical features such as chapter summaries and revision questions to enhance reader engagement, this text successfully blends economic theories with cutting-edge multidisciplinary insights. This second edition will be indispensable to anyone interested in how behavioural economics and finance can inform our understanding of consumers' and businesses' decisions and choices. It will appeal especially to undergraduate and graduate students but also to academic researchers, public policy-makers and anyone interested in deepening their understanding of how economics, psychology and sociology interact in driving our everyday decision-making.
Introducing behavioural economics -- Microeconomic principles -- Motivations and incentives -- Heuristics and bias -- Prospects and regrets -- Learning -- Time and plans -- Bad habits -- Sociality and identity -- Personality, moods and emotions -- Behavioural public policy -- Neuroeconomics I: Principles -- Neuroeconomics II: Evidence -- Behavioural finance -- Behavioural anomalies in finance -- Corporate investment and finance -- Emotional trading -- Macroeconomics and financial systems -- Behavioural macroeconomics and finance -- Financial instability and macroeconomic performance -- Happiness and wellbeing -- Bibliography -- Index.
Revised edition of the author's Behavioural economics and finance, 2013.
OCLC-licensed vendor bibliographic record.
Keywords: Economics -- Psychological aspects; Finance -- Psychological aspects; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Economics / Theory